Appropriation of the City by the Youth: Parks and Squares as Public Spaces. Issue 5 (March 2021) - Antonova, N; Abramova, S; Gurarii, A
Abstract: The article reports on the perception of young people to city parks and green squares as public spaces, or the "third place". Urban green space have multiple benefits for the physical and mental health and wellbeing of urban population. It acts as a factor of the formation of local identity and contributes to exercising the diversity of needs of different social groups. Based on a series of in-depth interviews (n=10), the article argues that the main barriers to attending parks are their remoteness from the place of residence and the lack of time. According to the respondents, an ideal park is divided into several zones according to the needs and interests of different social groups. It contains areas for walking, and playgrounds for children and teenagers. Young people attach particular importance to the landscaping of parks since the presence of flowers, trees, shrubs, lawns has a positive effect on the emotional state. In addition, city parks are expected to have such objects as benches, waste bins, toilets, and cafes. However, the respondents' opinions around the presence of event and entertainment industries are divided: some welcome such activities, whereas others share a negative attitude towards them. In general, parks and squares today are becoming a source of positive emotions and attitudes.